3(3x-1)=4(3x+1)

Simple and best practice solution for 3(3x-1)=4(3x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-1)=4(3x+1) equation:


3(3x-1)=4(3x+1)

We simplify the equation to the form, which is simple to understand
3(3x-1)=4(3x+1)

Reorder the terms in parentheses
+(+9x-3)=4*(3x+1)

Remove unnecessary parentheses
+9x-3=+4+*(+3x+1+)

Reorder the terms in parentheses
+9x-3=+(+12x+4)

Remove unnecessary parentheses
+9x-3=+12x+4

We move all terms containing x to the left and all other terms to the right.
+9x-12x=+4+3

We simplify left and right side of the equation.
-3x=+7

We divide both sides of the equation by -3 to get x.
x=-2.33333333333

See similar equations:

| x^3-11x^2+24x=3 | | 4-9a^2= | | (2x-5)=(x+30) | | 2(v-4)=8v+34 | | -2xy*3xy= | | 8-4x-(12-3x)= | | 80-(4x+7)=4(x+7)+x | | 2(2x-1)=3(x+1) | | x+73x=77 | | 6b^2+19b-36=0 | | 6(d+6)=4(d-6)-d | | -24(x-2)= | | 2(n+4)=8-6(n-4) | | -24(x+2)= | | -12(2x-12)= | | 2x-2y=-1 | | m+m(0.07)= | | 2x-3y+x+5y-3= | | y=5x-13 | | (57x+58y)+(-5x+41y)= | | (18x+2y)+(36x+27y)= | | (63x+50y)-(17x+35y)= | | (64x+48y)-(9x-16y)= | | 5x-3=-10x+8 | | 2x+8=-28 | | (30+5x)+(15+10x)=180 | | 6x+5=9x-19 | | 64-7x=2x+17 | | 2x+3x+1=12-6 | | 6x+14=-40 | | 8-9[9-(3y-7)]= | | 6-9x=29-16x |

Equations solver categories